2022
DOI: 10.1177/10497323221097247
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Professionals’ Experiences of Receiving Gratitude: A Transformative and Protective Resource

Abstract: Providing palliative care can be both challenging and rewarding. It involves emotionally demanding work and yet research shows that burnout is lower than in other fields of health care. Spontaneous expressions of gratitude from patients and family members are not uncommon and are highly valued. This study explored the experience of Spanish palliative professionals who received expressions of gratitude from their patients and families. A phenomenological approach was used to better understand the role of receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Previous research highlights gratitude as an important factor within subjective well-being (Aparicio et al, 2017) and suggested providing gratitude could positively impact both patients and healthcare staff (Day et al, 2020;Lanham et al, 2012). The present study adds to healthcare-based gratitude findings by Aparicio et al (2019) by indicating expressions of gratitude can form meaningful sources of feedback, supporting greater personal accomplishment and increased awareness of the impact of their work on patients within CAMHS inpatient settings.…”
Section: What This Study Adds To the Existing Evidencesupporting
confidence: 58%
See 1 more Smart Citation
“…Previous research highlights gratitude as an important factor within subjective well-being (Aparicio et al, 2017) and suggested providing gratitude could positively impact both patients and healthcare staff (Day et al, 2020;Lanham et al, 2012). The present study adds to healthcare-based gratitude findings by Aparicio et al (2019) by indicating expressions of gratitude can form meaningful sources of feedback, supporting greater personal accomplishment and increased awareness of the impact of their work on patients within CAMHS inpatient settings.…”
Section: What This Study Adds To the Existing Evidencesupporting
confidence: 58%
“…Over the past two decades gratitude in its many forms -and its association with subjective well-being (Aparicio et al, 2019)-has received considerable attention, with a growing body of literature specific to the benefits of gratitude for healthcare professionals (Day et al, 2020). For example, nurses offering or maintaining an attitude of gratitude found it helpful in providing emotional support to patients and in developing compassion and self-care (Lanham et al, 2012;Randolph, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Moreover, it seems that such expressions of gratitude may be beneficial for the patients 13 and even for the professionals receiving these expressions. 14,15 Initial studies mention specific aspects appreciated on each experience 16,17 but, to the best of our knowledge, there has been no in-depth analysis of what is the essence of the object of gratitude. Gratitude emerges as a response to something done altruistically by someone and perceived as good by the other.…”
Section: Introductionmentioning
confidence: 99%
“…In psychology, gratitude is defined as a transient, emotional state arising from a two-stage process: the recognition that a benefit has been received and the acknowledgment that such a benefit is derived from someone else's action (4)(5)(6)(7)(8). When gratitude is experienced more regularly over time, in the form of a more general disposition in noticing and appreciating positive aspects in the world, it is conceptualized as a personality trait more than an emotional state (9).…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, the role of gratitude has been investigated in the context of palliative care ( 7 , 9 , 18 , 21 23 ). The interest raises from the consideration that gratitude has been specifically linked with psychological constructs relevant for palliative care as anxiety ( 24 ) and death anxiety ( 25 , 26 ), depression ( 12 , 27 30 ), and psychological distress ( 30 ).…”
Section: Introductionmentioning
confidence: 99%